Simple silicone chamber system for 3D skeletal muscle tissue formation - Snyman, Celia; Goetsch, Kyle P.; Myburgh, Kathryn H.; Niesler, Carola U. (Frontiers in Physiology, 2013)
Bioengineering skeletal muscle often requires customized equipment and intricate casting techniques. One of the major hurdles when initially trying to establish in vitro tissue engineered muscle constructs is the lack of consistency across published methodology. Although this diversity allows for specialisation according to specific research goals, lack of standardisation hampers comparative efforts. Differences in cell type, number and density, variability in matrix and scaffold usage as well as inconsistency in the distance between and type of adhesion posts complicates initial establishment of the technique with confidence. We describe an inexpensive, but readily adaptable silicone chamber system for the generation of skeletal muscle constructs that can readily be standardized and used to elucidate myoblast behaviour in a three-dimensional space. Muscle generation, regeneration and adaptation can also be investigated in this model, which is more advanced than differentiated myotubes.